Acceleration of vascularized bone tissue-engineered constructs in a large animal model combining intrinsic and extrinsic vascularization - Weigand, Annika; Beier, Justus; Heß, Andreas; Gerber, Thomas; Arkudas, Andreas; Horch, Raymund E.; Boos, Anja (Tissue Engineering: Parts A, B, and C, 2015)
During the last decades, a range of excellent and promising strategies in Bone Tissue Engineering have been developed. However, the remaining major problem is the lack of vascularization. In this study, extrinsic and intrinsic vascularization strategies were combined for acceleration of vascularization. For optimal biomechanical stability of the defect site and simplifying future transition into clinical application, a primary stable and approved nanostructured bone substitute in clinically relevant size was used. An arteriovenous (AV) loop was microsurgically created in sheep and implanted, together with the bone substitute, in either perforated titanium chambers (intrinsic/extrinsic) for different time intervals of up to 18 weeks or isolated Teflon(®) chambers (intrinsic) for 18 weeks. Over time, magnetic resonance imaging and micro-computed tomography (CT) analyses illustrate the dense vascularization arising from the AV loop. The bone substitute was completely interspersed with newly formed tissue after 12 weeks of intrinsic/extrinsic vascularization and after 18 weeks of intrinsic/extrinsic and intrinsic vascularization. Successful matrix change from an inorganic to an organic scaffold could be demonstrated in vascularized areas with scanning electron microscopy and energy dispersive X-ray spectroscopy. Using the intrinsic vascularization method only, the degradation of the scaffold and osteoclastic activity was significantly lower after 18 weeks, compared with 12 and 18 weeks in the combined intrinsic-extrinsic model. Immunohistochemical staining revealed an increase in bone tissue formation over time, without a difference between intrinsic/extrinsic and intrinsic vascularization after 18 weeks. This study presents the combination of extrinsic and intrinsic vascularization strategies for the generation of an axially vascularized bone substitute in clinically relevant size using a large animal model. The additional extrinsic vascularization promotes tissue ingrowth and remodeling processes of the bone substitute. Extrinsic vessels contribute to faster vascularization and finally anastomose with intrinsic vasculature, allowing microvascular transplantation of the bone substitute after a shorter prevascularization time than using the intrinsic method only. It can be reasonably assumed that the usage of perforated chambers can significantly reduce the time until transplantation of bone constructs. Finally, this study paves the way for further preclinical testing for proof of the concept as a basis for early clinical applicability.
EVALuna2:15582

ADSCs and adipocytes are the main producers in the autotaxin-lysophosphatidic acid axis of breast cancer and healthy mammary tissue in vitro - Schmid, Rafael; Wolf, Katharina; Robering, Jan Willem; Strauss, Selina; Strissel, Pamela; Strick, Reiner; Rübner, Matthias; Fasching, Peter; Horch, Raymund E.; Kremer, Andreas; Boos, Anja; Weigand, Annika (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common malignancy in women affecting one out of eight females throughout their lives. Autotaxin (ATX) is upregulated in breast cancer which results in increased lysophosphatidic acid (LPA) formation within the tumor. This study's aim was to identify the role of different mammary cell populations within the ATX-LPA axis. METHODS: Epithelial-cell-adhesion-molecule-positive (EpCAM) and -negative cells from breast tumors, adipose-derived stem cells (ADSCs) of tumor-adjacent and tumor-distant mammary fat were isolated and compared to healthy ADSCs, mammary epithelial cells (HMECs), and mesenchymal cells (MES) of healthy mammary tissue (n = 4 each) and further to well-established breast (cancer) cell lines. RESULTS: mRNA expression analyses revealed that ADSCs and MES largely expressed LPA receptor 1 (LPAR1) while epithelial cells mainly expressed LPAR6. LPA 18:1 activated all the cell populations and cell lines by rise in cytosolic free calcium concentrations. MES and ADSCs expressed ATX whereas epithelial cells did not. ADSCs revealed the highest expression in ATX with a significant decline after adipogenic differentiation in healthy ADSCs, whereas ATX expression increased in ADSCs from tumor patients. Breast (cancer) cell lines did not express ATX. Transmigration of MES was stimulated by LPA whereas an inhibitory effect was observed in epithelial cells with no differences between tumors and healthy cells. Triple-negative breast cancer (TNBC) cell lines were also stimulated and the transmigration partly inhibited using the LPA receptor antagonist Ki16425. CONCLUSIONS: We here show that each mammary cell population plays a different role in the ATX-LPA axis with ADSCs and adipocytes being the main source of ATX in tumor patients in our experimental setting. Inhibitors of this axis may therefore present a valuable target for pharmacological therapies.
EVALuna2:35125

An Innovative Arteriovenous (AV) Loop Breast Cancer Model Tailored for Cancer Research - An, Ran; Strissel, Pamela; Al-Abboodi, Majida; Robering, Jan Willem; Reakasame, Supachai; Eckstein, Markus; Peddi, Ajay; Hauck, Theresa; Bäuerle, Tobias; Boccaccini, Aldo R.; Youssef, Almoatazbellah; Sun, Jiaming; et al. (Bioengineering, 2022)
Animal models are important tools to investigate the pathogenesis and develop treatment strategies for breast cancer in humans. In this study, we developed a new three-dimensional in vivo arteriovenous loop model of human breast cancer with the aid of biodegradable materials, including fibrin, alginate, and polycaprolactone. We examined the in vivo effects of various matrices on the growth of breast cancer cells by imaging and immunohistochemistry evaluation. Our findings clearly demonstrate that vascularized breast cancer microtissues could be engineered and recapitulate the in vivo situation and tumor-stromal interaction within an isolated environment in an in vivo organism. Alginate–fibrin hybrid matrices were considered as a highly powerful material for breast tumor engineering based on its stability and biocompatibility. We propose that the novel tumor model may not only serve as an invaluable platform for analyzing and understanding the molecular mechanisms and pattern of oncologic diseases, but also be tailored for individual therapy via transplantation of breast cancer patient-derived tumors.
CRIS-Team Scopus Importer:2022-07-15
Keywords: animal model; arteriovenous loop; breast cancer

A novel early precursor cell population from rat bone marrow promotes angiogenesis in vitro - Brandl, Anna; Yuan, Quan; Boos, Anja; Beier, Justus; Arkudas, Andreas; Kneser, Ulrich; Horch, Raymund E.; Bleiziffer, Oliver (Bmc Cell Biology, 2014)
Some studies demonstrated therapeutic angiogenesis attributable to the effects of endothelial progenitor cells (EPC), others have reported disappointing results. This may be due to the fact that EPC populations used in these contradictory studies were selected and defined by highly variable and differing experimental protocols. Indeed, the isolation and reliable characterization of ex vivo differentiated EPC raises considerable problems due to the fact there is no biomarker currently available to specifically identify EPC exclusively. On the other hand traditional differentiation of primary immature bone marrow cells towards the endothelial lineage is a time-consuming process of up to 5 weeks. To circumvent these shortcomings, we herein describe a facile method to isolate and enrich a primary cell population from rat bone marrow, combining differential attachment methodology with cell sorting technology.The combination of these techniques enabled us to obtain a pure population of early endothelial precursor cells that show homogenous upregulation of CD31 and VEGF-R2 and that are positive for CD146. These cells exhibited typical sprouting on Matrigel(TM). Additionally, this population displayed endothelial tube formation when resuspended in Matrigel(TM) as well as in fibrin glue, demonstrating its functional angiogenic capacity. Moreover, these cells stained positive for DiI-ac-LDL and FITC-UEA, two markers that are commonly considered to stain differentiating EPCs. Based upon these observations in this study we describe a novel and time-saving method for obtaining a pure endothelial precursor cell population as early as 2-3 weeks post isolation that exhibits endothelial abilities in vitro and which still might have retained its early endothelial lineage properties.The rapid isolation and the high angiogenic potential of these syngeneic cells might facilitate and accelerate the pre-vascularization of transplanted tissues and organs also in a human setting in the future.
EVALuna2:15558

Autologous serum improves bone formation in a primary stable silica-embedded nanohydroxyapatite bone substitute in combination with mesenchymal stem cells and rhBMP-2 in the sheep model - Boos, Anja; Weigand, Annika; Deschler, Gloria; Gerber, Thomas; Arkudas, Andreas; Kneser, Ulrich; Horch, Raymund E.; Beier, Justus (International Journal of Nanomedicine, 2014)
New therapeutic strategies are required for critical size bone defects, because the gold standard of transplanting autologous bone from an unharmed area of the body often leads to several severe side effects and disadvantages for the patient. For years, tissue engineering approaches have been seeking a stable, axially vascularized transplantable bone replacement suitable for transplantation into the recipient bed with pre-existing insufficient conditions. For this reason, the arteriovenous loop model was developed and various bone substitutes have been vascularized. However, it has not been possible thus far to engineer a primary stable and axially vascularized transplantable bone substitute. For that purpose, a primary stable silica-embedded nanohydroxyapatite (HA) bone substitute in combination with blood, bone marrow, expanded, or directly retransplanted mesenchymal stem cells, recombinant human bone morphogenetic protein 2 (rhBMP-2), and different carrier materials (fibrin, cell culture medium, autologous serum) was tested subcutaneously for 4 or 12 weeks in the sheep model. Autologous serum lead to an early matrix change during degradation of the bone substitute and formation of new bone tissue. The best results were achieved in the group combining mesenchymal stem cells expanded with 60 ?g/mL rhBMP-2 in autologous serum. Better ingrowth of fibrovascular tissue could be detected in the autologous serum group compared with the control (fibrin). Osteoclastic activity indicating an active bone remodeling process was observed after 4 weeks, particularly in the group with autologous serum and after 12 weeks in every experimental group. This study clearly demonstrates the positive effects of autologous serum in combination with mesenchymal stem cells and rhBMP-2 on bone formation in a primary stable silica-embedded nano-HA bone grafting material in the sheep model. In further experiments, the results will be transferred to the sheep arteriovenous loop model in order to engineer an axially vascularized primary stable bone replacement in clinically relevant size for free transplantation.
EVALuna2:15577

Bildgebende Diagnostik zur Therapieplanung bei Lip- und Lymphödem - Zetzmann, Katharina; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja (Phlebologie, 2020)
Lipoedema is a progressive disease, which predominantly affects women. It is characterised by circumferential growth, with increase in fat tissue of the extremities, and can lead to oedema. In contrast, the lymphoedema is defined by a specific lymphatic drainage disorder and can lead to fibrosis of the surrounding connective tissue. While lipoedema is diagnosed through clinical symptoms and diagnostic imaging can usually only be used to rule out comorbidities, lymphatic drainage disorder can be visualised using imaging methods. Ultrasound is a basis diagnostic tool to show retained interstitial fluid in lip-and lymphoedema. Lymphoscintigraphy is considered to be the gold standard to demonstrate a lymphatic drainage disorder, which can be combined with computed tomography. Indocyanine green(ICG) lymphography is a dynamic imaging tool, which is of increasing significance due to its possible intraoperative use. Magnetic resonance imaging (MRI) lymphography has the ability to visualise a lymphoedema and a lymphatic drainage disorder in three dimensions and is therefore considered to be a meaningful supplement. Therapy of lip-and lymphoedema should always be based on a combination of conservative and surgical strategies. While liposuction and other resection procedures can lead to symptom relief in lipedoema or advanced lymphoedema, newer reconstructive pro cedures such as lymph node transplantation or lymphovenous anastomoses are modern techniques to treat lymphoedema. A long lasting volume reduction can be achieved by creating new lymphatic pathways leading to improved quality of life and reduced symptoms.
CRIS-Team Scopus Importer:2020-05-02
Keywords: liposuction

Body Contouring Surgery Improves Physical Activity in Patients After Massive Weight Loss—a Retrospective Study - Maringa, Linda; Hauck, Theresa; Boos, Anja; Schmitz, Marweh; Arkudas, Andreas; Horch, Raymund E.; Ludolph, Ingo; Cai, Aijia (Obesity Surgery, 2019)
Background: The aim of the study was to compare physical activity (PA) in patients who had undergone massive weight loss (MWL), before and after body contouring procedures. Methods: All patients undergoing body contouring surgery after MWL between 2007 and 2017 with a minimum follow-up of 6 months after the last procedure were included in this retrospective study. Excluded were those with a body mass index > 35 kg/m2 and those with comorbidities leading to impaired PA. Quality of life (QOL) was assessed using the Moorehead-Ardelt QOL Questionnaire II. Evaluation of PA was obtained with the International Physical Activity Questionnaire (IPAQ) short form and the Freiburg PA Questionnaire. Functional impairment during exercise was analyzed using a self-designed functional impairment score (FIS). Results: In the 45 patients completing the survey (37 female, 8 male), an improvement in QOL (p < 0.001) and PA scored by the IPAQ (p = 0.017) was found. The Freiburg PA Questionnaire showed no difference in PA before and after body contouring surgery (p = 0,274). Furthermore, scores of the FIS indicated a decrease of functional impairment during physical activity after body contouring surgery (p < 0.001). Conclusion: Body contouring improves QOL and PA in patients after massive weight loss. The results of our study confirm the important role of plastic surgery in the treatment and maintenance of health of patients with former obesity.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Body contouring surgery; Massive weight loss; Physical activity; Quality of life

Bone Tissue Engineering Under Xenogeneic-Free Conditions in a Large Animal Model as a Basis for Early Clinical Applicability - Weigand, Annika; Beier, Justus; Schmid, Rafael; Knorr, Thomas; Kilian, David; Goetzl, Rebekka; Gerber, Thomas; Horch, Raymund E.; Boos, Anja (Tissue Engineering: Parts A, B, and C, 2017)
For decades, researchers have been developing a range of promising strategies in bone tissue engineering with the aim of producing a significant clinical benefit over existing therapies. However, a major problem concerns the traditional use of xenogeneic substances for the expansion of cells, which complicates direct clinical transfer. The study's aim was to establish a totally autologous sheep model as a basis for further preclinical studies and future clinical application. Ovine mesenchymal stromal cells (MSC) were cultivated in different concentrations (0%, 2%, 5%, 10%, and 25%) of either autologous serum (AS) or fetal calf serum (FCS). With an increase of serum concentration, enhanced metabolic activity and proliferation could be observed. There were minor differences between MSC cultivated in AS or FCS, comparing gene and protein expression of osteogenic and stem cell markers, morphology, and osteogenic differentiation. MSC implanted subcutaneously in the sheep model, together with a nanostructured bone substitute, either in stable block or moldable putty form, induced similar vascularization and remodeling of the bone substitute irrespective of cultivation of MSC in AS or FCS and osteogenic differentiation. The bone substitute in block form together with MSC proved particularly advantageous in the induction of ectopic bone formation compared to the cell-free control and putty form. It could be demonstrated that AS is suitable for replacement of FCS for cultivation of ovine MSC for bone tissue engineering purposes. Substantial progress has been made in the development of a strictly xenogeneic-free preclinical animal model to bring future clinical application of bone tissue engineering strategies within reach.
EVALuna2:32847

Cancer research by means of tissue engineering - is there a rationale? - Horch, Raymund E.; Boos, Anja; Yuan, Quan; Bleiziffer, Oliver; Detsch, Rainer; Boccaccini, Aldo R.; Alexiou, Christoph; Sun, Jiaming; Beier, Justus; Arkudas, Andreas (Journal of Cellular and Molecular Medicine, 2013)
Tissue engineering (TE) has evoked new hopes for the cure of organ failure and tissue loss by creating functional substitutes in the laboratory. Besides various innovations in the context of Regenerative Medicine (RM), TE also provided new technology platforms to study mechanisms of angiogenesis and tumour cell growth as well as potentially tumour cell spreading in cancer research. Recent advances in stem cell technology - including embryonic and adult stem cells and induced pluripotent stem cells - clearly show the need to better understand all relevant mechanisms to control cell growth when such techniques will be administered to patients. Such TE-Cancer research models allow us to investigate the interactions that occur when replicating physiological and pathological conditions during the initial phases of replication, morphogenesis, differentiation and growth under variable given conditions. Tissue microenvironment has been extensively studied in many areas of TE and it plays a crucial role in cell signalling and regulation of normal and malignant cell functions. This article is intended to give an overview on some of the most recent developments and possible applications of TE and RM methods with regard to the improvement of cancer research with TE platforms. The synthesis of TE with innovative methods of molecular biology and stem-cell technology may help investigate and potentially modulate principal phenomena of tumour growth and spreading, as well as tumour-related angiogenesis. In the future, these models have the potential to investigate the optimal materials, culture conditions and material structure to propagate tumour growth. © 2013 The Authors.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.cancer
Keywords: Angiogenesis; AV loop; Cancer research; Cell transplantation; in vitro tumour models; Metastasis; Telocytes; Tissue engineering; Tumour cells; Tumour growth; Tumourgenesis

Changes of perfusion patterns of surgical wounds under application of closed incision negative pressure wound therapy in postbariatric patients - Renno, Isabell; Boos, Anja; Horch, Raymund E.; Ludolph, Ingo (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Negative pressure wound therapy applied over closed incisions (ciNPT) has been shown to influence wound healing. Therefore, the aim of this study was to examine the short-term effects of ciNPT on skin perfusion patterns in postbariatric wounds.
CRIS-Team WoS Importer:2019-08-20

Comment on 'Basic concepts regarding fractures healing and the current options and future directions in managing bone fractures' - Weigand, Annika; Horch, Raymund E.; Beier, Justus; Arkudas, Andreas; Boos, Anja (International Wound Journal, 2016)
EVALuna2:15604

Comment on "Microsurgical Techniques Used to Construct the Vascularized and Neurotized Tissue Engineered Bone" - Weigand, Annika; Beier, Justus; Arkudas, Andreas; Horch, Raymund E.; Boos, Anja (BioMed Research International, 2015)
EVALuna2:15590

Comments on: "In vivo bone regeneration using tubular perfusion system bioreactor cultured nanofibrous scaffolds" vascularization–one challenge of tissue engineering - Weigand, Annika; Boos, Anja; Beier, Justus; Horch, Raymund E. (Tissue Engineering: Parts A, B, and C, 2014)
EVALuna2:15563

Cracking the perfusion code?: Laser-assisted Indocyanine Green angiography and combined laser Doppler spectrophotometry for intraoperative evaluation of tissue perfusion in autologous breast reconstruction with DIEP or ms-TRAM flaps - Ludolph, Ingo; Arkudas, Andreas; Schmitz, Marweh; Boos, Anja; Taeger, Christian; Rother, Ulrich; Horch, Raymund E.; Beier, Justus (Journal of Plastic Reconstructive and Aesthetic Surgery, 2016)
The aim of this prospective study was to assess the correlation of flap perfusion analysis based on laser-assisted Indocyanine Green (ICG) angiography with combined laser Doppler spectrophotometry in autologous breast reconstruction using free DIEP/ms-TRAM flaps. Between February 2014 and July 2015, 35 free DIEP/ms-TRAM flaps were included in this study. Besides the clinical evaluation of flaps, intraoperative perfusion dynamics were assessed by means of laser-assisted ICG angiography and post-capillary oxygen saturation and relative haemoglobin content (rHb) using combined laser Doppler spectrophotometry. Correlation of the aforementioned parameters was analysed, as well as the impact on flap design and postoperative complications. Flap survival rate was 100%. There were no partial flap losses. In three cases, flap design was based on the angiography, contrary to clinical evaluation and spectrophotometry. The final decision on the inclusion of flap areas was based on the angiographic perfusion pattern. Angiography and spectrophotometry showed a correlation in most of the cases regarding tissue perfusion, post-capillary oxygen saturation and relative haemoglobin content. Laser-assisted ICG angiography is a useful tool for intraoperative evaluation of flap perfusion in autologous breast reconstruction with DIEP/ms-TRAM flaps, especially in decision making in cases where flap perfusion is not clearly assessable by clinical signs and exact determination of well-perfused flap margins is difficult to obtain. It provides an objective real-time analysis of flap perfusion, with high sensitivity for the detection of poorly perfused flap areas. Concerning the topographical mapping of well-perfused flap areas, laser-assisted angiography is superior to combined laser Doppler spectrophotometry.
EVALuna2:15280

Dermal penetration and resorption of beta-naphthylamine and N-phenyl-beta-naphthylamine from lubricants in an ex vivo human skin model - Dennerlein, Kathrin; Göen, Thomas; Zobel, Melanie; Boos, Anja; Drexler, Hans; Kilo, Sonja (Chemosphere, 2017)
Dermal Penetration of aromatic amines (AA's), often suspected or known to be carcinogenic, can play an important role in the overall human exposure. However, information on penetration of certain AA's is poor and inconsistent. Penetration of the former lubricant additive N-phenyl-beta-naphthylamine (PBNA) and its contaminant beta-naphthylamine (BNA) a known carcinogen was investigated and the influence of formulation and co-application characterized. Percutaneous penetration of BNA and PBNA through freshly excised human skin (n = 8; 48 h) was investigated using an ex vivo diffusion cell model. Both AA's were applied in a technical-conform lubricant or dissolved in hexane. The amount of BNA and PBNA applied to skin was 0.52 and 259 ?g/0.64 cm2. The analytical determination of AA's was performed by GC-MS. Both, BNA and PBNA penetrated through human skin (38 vs. 5% of applied dose). In contrast to BNA, the percutaneous penetration of PBNA continued beyond the end of exposure. Co-exposure of both AA's increased the intradermal uptake of BNA and PBNA (p < 0.05). Exposure in lubricant showed the least overall penetration (2.9 and 1.9% of applied dose). The results clearly reveal that dermal penetration of both AA's depends strongly on the mode of application. Co-application and formulation alters the penetration of the AA's.
EVALuna2:9769

Development of an Innovative Cell Isolation Method for the Investigation of Breast Cancer Pathogenesis and Angiogenesis for Experimental In Vitro And In Vivo Assays - Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2017)
Background Breast cancer is the world's most common cancer among women. Autologous lipotransfer is increasingly used for breast reconstruction following surgical removal of the tumour. In cell-assisted lipotransfer, the transplant is enriched with stem cells from adipose tissue (ADSC). Despite positive clinical results, there are some concerns regarding oncological safety due to transplanted stem cells. To date there are only a few breast cancer studies using primary cells from the same patient to enable further investigation into the complexity of cell-cell interactions in breast cancer in an experimental setting.Materials and methodsWe performed literature research on the topic of autologous lipotransfer. 5 different cell types (epithelial, mesenchymal cells, ADSC, endothelial cells, endothelial progenitor cells) were isolated from mammary (carcinoma) tissue or blood and were subsequently characterised for gene and protein expression as well as functional properties. The arteriovenous (AV) loop model in the rat was evaluated as a possible in vivo model for breast cancer pathogenesis and angiogenesis in this study.ResultsThe literature provided evidence for an in-vitro interaction between ADSC and cells of the mammary (carcinoma) tissue. In some clinical studies, certain subgroups of patients appeared to be exposed to an increased risk of tumour recurrence after lipotransfer, but in most studies no correlation between lipotransfer and tumour recurrence was found. Different cell populations, which differed significantly in terms of surface markers, gene expression and functional properties, were isolated from tissue of the same patient. Axial vascularised tissue was successfully generated in the AV loop model.ConclusionIn this study we were able to isolate different cell populations from the same patient, which reflect the heterogeneity of the tumour tissue. This enables a precise analysis of cell-cell interactions and their effects on tumour angiogenesis and pathogenesis in breast cancer. In combination with the AV loop model, this offers new possibilities to generate vascularised mammary carcinoma tissue as well as healthy mammary gland tissue in vivo as an optimal model for the clinical setting.
EVALuna2:32854

Establishment and Evaluation of a Microsurgery Course for Medical Students - Beier, Justus; Horch, Raymund E.; Boos, Anja; Taeger, Christian; Breuer, Georg; Arkudas, Andreas (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2015)
Very few microsurgical courses have been offered for medical students in Germany to date. To raise early interest in this technique, which is essential for plastic and reconstructive surgery, and to guide eligible medical students to choose plastic surgery as their specialist field, the Department of Plastic and Hand Surgery, supported by the Faculty of Medicine of the Friedrich-Alexander-University of Erlangen-Nuremberg, implemented a microsurgical course for students in 2011. This study describes the implementation of that course and evaluates its impact on the subsequent choice of the participants' specialist fields.Since the summer of 2011, the microsurgery course for medical students has taken place regularly 3 times per term. It is free of charge for participants and is guided by senior physicians of the Department of Plastic and Hand Surgery together with student tutors from the Faculty of Medicine. The arterial end-to-end anastomosis in the fresh chicken leg is used as a training model. Based on a questionnaire survey the participants were evaluated and statistically analysed regarding their course satisfaction, self-assessment of their own eligibility before and after the course, the anticipated future choice of their medical specialist field and how their choice was influenced by this course.After the successful implementation of the microsurgical course in 2011, a significant number of students were interested in microsurgery. According to the questionnaire, the level of enthusiasm was high among all participants. The self-assessment of microsurgical skills improved significantly after the course compared with the pre-course assessment. In 82% of the participants, the course had a strong positive influence on the future choice of their specialist field.The regular implementation of a microsurgical course for students in the form described here is practicable and possible without undue personnel and cost of materials. The ongoing interest among students in such an offer is enormous and the satisfaction of the participants is very high. This might be a way to recruit future plastic surgeons by raising early enthusiasm for microsurgery. These future plastic surgeons, in turn, would be given the chance to experience a very fascinating aspect of plastic surgery, which might help them to decide on their specialisation within that field at a later point in their career.
EVALuna2:15603

Etablierung und Evaluation einer multinationalen Wissenschaftsakademie: Ein neues Modell zur Stärkung des wissenschaftlichen Nachwuchses in der mikrochirurgischen Forschung – Ein Konsensus Papier der DAM - Horch, Raymund E.; Kengelbach-Weigand, Annika; Pierer, G.; Kneser, U.; Schaefer, D.; Boos, Anja; Arkudas, Andreas; Schmidt, V. J. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2020)
BACKGROUND: The formation of professional networks and cooperations - in addition to any qualified good education - seems fundamental for a successful career. In a number of disciplines, various symposia or conferences exist. In the field of microsurgery, however, a specific, guided and designated opportunity for junior scientists to network with one another has been missing so far. METHODS: In 2017, a science academy was initiated for the first time by the German-speaking Association for Nerves and Vessels (DAM) with the goal of bringing together and networking microsurgically researching young physicians and scientists. This was intended to happen on a small scale once a year in order to develop synergies for joint research projects. For this purpose, motivated junior researchers were individually selected by their mentors and sent to the academy by the boards of research institutions that are organized in the DAM. After getting to know each other in a relaxed atmosphere, the participants were given the opportunity to present their respective research project within the framework of thematic blocks and moderated by experienced mentors. Each presentation was followed by a round table discussion and small group work, in which knowledge and methods were exchanged and points of contact for possible later cooperation were identified. RESULTS: In the past 3 years, the DAM Science Academy proved to be an optimal format to initiate and promote networks of young researchers comprising microsurgically interested physicians and scientists. There were many lively and in-depth discussions, which were mainly due to the open working atmosphere and the obligation to confidentiality. Most of the synergies were shown i. a. in the field of angiogenesis, bioreactor, carcinoma-ADSC interactions, stem cells, AV loop model, ischemia/reperfusion, and nerve regeneration. The participants consistently gave a very positive feedback in the final evaluation with the wish to continue this academy. CONCLUSION: The DAM Science Academy can be considered a highly suitable complemental platform to the existing networking opportunities among microsurgical researchers. Experience so far suggests that this will hopefully result in long-term cooperations and a permanent transfer of knowledge among the participants.
CRIS-Team Scopus Importer:2020-04-17

Growth factors IGF-1 and KGF and adipose-derived stem cells promote migration and viability of primary human keratinocytes in an in vitro wound model - Stadelmann, Nina; Horch, Raymund E.; Schmid, Rafael; Ostendorf, David; Peddi, Ajay; Promny, Theresa; Boos, Anja; Kengelbach-Weigand, Annika (Frontiers in Medicine, 2025)
Introduction: In the field of plastic surgery, epidermal transplantation is a potential treatment for chronic wounds that results in only minor donor site morbidity. Improving the regenerative capacities of epidermal grafts or single-cell suspensions and therefore accelerating healing processes would be of significant interest. Methods: In the present study, we analyzed the effects of growth factors and adipose-derived stem cells (ADSCs) on keratinocyte properties. For optimum translation into the clinical setting, primary human keratinocytes and patient-matched ADSCs were isolated and used in an in vitro wound model. Results: The keratinocyte migration and viability increased after treatment with the growth factors insulin-like growth factor 1 (IGF-1) and keratinocyte growth factor (KGF). A similar effect was observed with the use of a concentrated ADSC-conditioned medium (ADSC-CM). It was further possible to isolate the keratinocytes in a xenogen-free medium, which is essential for clinical translation. Importantly, a patient-dependent influence on the effects of the growth factors and ADSC-CM was observed. Discussion: This study provides potential for the improvement of epidermal transplantation in the treatment of chronic wounds using xenogen-free isolated and cultivated keratinocytes, growth factors, and ADSC. Translating these results into clinical application may help accelerate wound healing and shorten the time until patients can return to everyday life.
CRIS-Team Scopus Importer:2025-02-28
Keywords: adipose-derived stem cells; conditioned medium; growth factors; keratinocytes; wound healing

Human adipose-derived stem cells support lymphangiogenesis in vitro by secretion of lymphangiogenic factors - Ahmadzadeh, Nima; Robering, Jan Willem; Kengelbach-Weigand, Annika; Al-Abboodi, Majida; Beier, Justus; Horch, Raymund E.; Boos, Anja (Experimental Cell Research, 2020)
Lymphedema is a chronic progressive disease ultimately resulting in severe, disfiguring swelling and permanent changes of the affected tissues. Presently, there is no causal treatment approach of lymphedema. Therefore, most therapies are purely symptomatic. However, the recent use of stem cell-based therapies has offered new prospects for alternative treatment options. The present study was performed to investigate the effects of human adipose-derived stem cells (ADSCs) on human dermal lymphatic endothelial cells (HDLECs) in terms of basic in vitro lymphangiogenic assays (WST-8 assay, scratch assay, transmigration assay, sprouting assay, tube formation assay). The influence of ADSC-conditioned medium (ADSC-CM) on HDLECs was compared to recombinant VEGF-C, bFGF and HGF. Further ADSC-CM was characterized by protein microarray and enzyme-linked immunosorbent assay (ELISA). Although key-lymphangiogenic growth factors - like VEGF-C - could only be detected in low concentrations within the conditioned medium (CM), HDLECs were potently stimulated to proliferate, migrate and to form tube like structures by ADSC-CM. Despite concentrations more than hundredfold higher than those found in the conditioned medium, stimulation with recombinant VEGF-C, bFGF and HGF was still weaker compared to ADSC-CM. These results highlight the effectiveness of growth factors secreted by ADSC to stimulate HDLEC, potentially providing a promising new therapeutic approach for the treatment of lymphedema.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Adipose-derived stem cells (ADSCs); Cell therapy; Human dermal lymphatic endothelial cells (HDLECs); Lymphangiogenesis; Lymphedema; Secretome

Imaging for treatment planning in lipo-and lymphedema - Zetzmann, Katharina; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
Lipoedema is a progressive disease, which predominantly affects women. It is characterised by circumferential growth, with increase in fat tissue of the extremities, and can lead to oedema. In contrast, the lymphoedema is defined by a specific lymphatic drainage disorder and can lead to fibrosis of the surrounding connective tissue. While lipoedema is diagnosed through clinical symptoms and diagnostic imaging can usually only be used to rule out comorbidities, lymphatic drainage disorder can be visualised using imaging methods. Ultrasound is a basis diagnostic tool to show retained interstitial fluid in lip- and lymphoedema. Lymphoscintigraphy is considered to be the gold standard to demonstrate a lymphatic drainage disorder, which can be combined with computed tomography. Indocyanine green(ICG) lymphography is a dynamic imaging tool, which is of increasing significance due to its possible intraoperative use. Magnetic resonance imaging (MRI) lymphography has the ability to visualise a lymphoedema and a lymphatic drainage disorder in three dimensions and is therefore considered to be a meaningful supplement. Therapy of lip- and lymphoedema should always be based on a combination of conservative and surgical strategies. While liposuction and other resection procedures can lead to symptom relief in lipedoema or advanced lymphoedema, newer reconstructive procedures such as lymph node transplantation or lymphovenous anastomoses are modern techniques to treat lymphoedema. A long lasting volume reduction can be achieved by creating new lymphatic pathways leading to improved quality of life and reduced symptoms.
EVALuna2:211463

Interdisciplinary Treatment for Cutaneous Abdominal Wall Metastasis from Cervical Cancer with Resection and Reconstruction of the Abdominal Wall Using Free Latissimus Dorsi Muscle Flap: A Case Report - Boos, Anja; Beckmann, Matthias; Horch, Raymund E.; Beier, Justus (Geburtshilfe und Frauenheilkunde, 2014)
EVALuna2:15567

Intra- and Postoperative Blood Flow Monitoring in a Sheep Model of Uterus Transplantation - Kengelbach-Weigand, Annika; Lotz, Laura; Schmid, Rafael; Lang, Werner; Beckmann, Matthias; Hoffmann, Inge; Horch, Raymund E.; Renner, Stefan; Dittrich, Ralf; Boos, Anja; Hildebrandt, Thomas (In Vivo, 2019)
Background: The introduction of the opportunity to transplant a viable uterus into women for fulfilling their desire to have a child has awakened high expectations worldwide. Materials and Methods: A sheep model was used to evaluate tools for optimizing measurement of blood flow in uterine transplantation. Intraoperatively, blood flow was measured using unidirectional Doppler and indocyanine green (ICG) fluorescence imaging. Postoperatively, an implantable Doppler probe served as a tool for clinical monitoring the patency of anastomosed vessels. Results: ICG imaging showed complete vascularization of the uterus before and in short-term evaluation after surgery. The implantable Doppler probe proved to be highly suitable for assessing patency of vessels in a non-invasive way. Results of histology, and real-time polymerase chain reaction demonstrated viability of the transplanted uterus. Conclusion: Different methods to monitor vasculature patency have proven to be advantageous in supporting both surgeons and researchers in ensuring successful implementation of uterine transplantation.
CRIS-Team WoS Importer:2019-03-08

Management of extremely hard-to-heal extremity wounds with severe life-threatening complications - Cai, Aijia; Boos, Anja; Arkudas, Andreas; Horch, Raymund E. (International Wound Journal, 2017)
The introduction of neoadjuvant radiotherapy has allowed limb-preserving surgical treatment in patients with extremity soft tissue sarcoma, and the overall prognosis of this approach is similar to that of limb amputation. The benefits of this treatment, however, are often accompanied with a higher risk of major complications and blood vessel damage because of radiation-induced inflammation and necrosis of the vessel wall. In particular, it is associated with the rupture of large vessels like the femoral artery and more severe complications of wounds located in the proximal lower extremity. We present a series of four patients with soft tissue sarcoma of the thigh undergoing tumour removal and reconstruction of the defect after neoadjuvant radiotherapy. The post-operative outcome depended on the total dose of radiation used as well as the closing technique of the resulting wound. Major wound complications occurred when the irradiated skin was closed directly over the resection cavity or when local skin flaps were used. In one case, severe radiation-induced life-threatening multiple bleeding events occurred, which led to multiple flap failures. Even if the skin cover is not a problem, we propose a combined interdisciplinary approach involving immediate plastic surgical transfer of healthy, well-vascularised tissue into a defect resulting from oncological resection of sarcoma of the lower extremity following neoadjuvant radiotherapy in order to avoid secondary wound breakdown and severe bleeding complications.
EVALuna2:32842

Mesenchymal stem cells and myoblast differentiation under HGF and IGF-1 stimulation for 3D skeletal muscle tissue engineering - Witt, Ramona; Weigand, Annika; Boos, Anja; Dippold, Dirk; Boccaccini, Aldo R.; Schubert, Dirk W.; Hardt, Moritz; Lange, Claudia; Arkudas, Andreas; Horch, Raymund E.; Beier, Justus; Cai, Aijia (Bmc Cell Biology, 2017)
Keywords: Mesenchymal stem cells; Myogenic differentiation; HGF; IGF-1; PCL-collagen nanofibers; Skeletal muscle tissue engineering

Mesenchymal stem cells and myoblast differentiation under HGF and IGF-1 stimulation for 3D skeletal muscle tissue engineering - Witt, Ramona; Weigand, Annika; Boos, Anja; Dippold, Dirk; Schubert, Dirk W.; Boccaccini, Aldo R.; Arkudas, Andreas; Horch, Raymund E.; Beier, Justus (Bmc Cell Biology, 2017)
Keywords: HGF; IGF-1; Mesenchymal stem cells; Myogenic differentiation; PCL-collagen nanofibers; Skeletal muscle tissue engineering

Mesenchymal stem cells promote lymphangiogenic properties of lymphatic endothelial cells - Robering, Jan Willem; Weigand, Annika; Pfuhlmann, Romy; Horch, Raymund E.; Beier, Justus; Boos, Anja (Journal of Cellular and Molecular Medicine, 2018)
Lymphatic metastasis is one of the main prognostic factors concerning long-term survival of cancer patients. In this regard, the molecular mechanisms of lymphangiogenesis are still rarely explored. Also, the interactions between stem cells and lymphatic endothelial cells (LEC) in humans have not been well examined. Therefore, the main objective of this study was to assess the interactions between mesenchymal stem cells (MSC) and LEC using in vitro angiogenesis assays. Juvenile LEC were stimulated with VEGF-C, bFGF, MSC-conditioned medium (MSC-CM) or by co-culture with MSC. LEC proliferation was assessed using a MTT assay. Migration of the cells was determined with a wound healing assay and a transmigration assay. To measure the formation of lymphatic sprouts, LEC spheroids were embedded in collagen or fibrin gels. The LEC's capacity to form capillary-like structures was assessed by a tube formation assay on Matrigel® . The proliferation, migration and tube formation of LEC could be significantly enhanced by MSC-CM and by co-culture with MSC. The effect of stimulation with MSC-CM was stronger compared to stimulation with the growth factors VEGF-C and bFGF in proliferation and transmigration assays. Sprouting was stimulated by VEGF-C, bFGF and by MSC-CM. With this study, we demonstrate the potent stimulating effect of the MSC secretome on proliferation, migration and tube formation of LEC. This indicates an important role of MSC in lymphangiogenesis in pathological as well as physiological processes.
EVALuna2:211472

Myogenic differentiation of primary myoblasts and mesenchymal stromal cells under serum-free conditions on PCL-collagen I-nanoscaffolds - Arkudas, Andreas; Weigand, Annika; Beier, Justus; Horch, Raymund E.; Hardt, Moritz; Schneider, Paul; Schmid, Rafael; Lange, Claudia; Dippold, Dirk; Schubert, Dirk W.; Boos, Anja; Cai, Aijia (BMC Biotechnology, 2018)
The creation of functional skeletal muscle via tissue engineering holds great promise without sacrificing healthy donor tissue. Different cell types have been investigated regarding their myogenic differentiation potential under the influence of various media supplemented with growth factors. Yet, most cell cultures include the use of animal sera, which raises safety concerns and might lead to variances in results. Electrospun nanoscaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability. We therefore aimed to develop a serum-free myogenic differentiation medium for the co-culture of primary myoblasts (Mb) and mesenchymal stromal cells derived from the bone marrow (BMSC) and adipose tissue (ADSC) on electrospun poly-ε-caprolacton (PCL)-collagen I-nanofiber
Keywords: Nanoscaffolds; Myogenic differentiation; Myoblasts; Mesenchymal stromal cells; Serum-free media; BMSC; Electrospun PCL-collagen I-nanofibers; ADSC

Myogenic differentiation of primary myoblasts and mesenchymal stromal cells under serum-free conditions on PCLcollagen I-nanoscaffolds - Hardt, Moritz; Schneider, Paul; Schmid, Rafael; Lange, Claudia; Dippold, Dirk; Schubert, Dirk W.; Boos, Anja; Weigand, Annika; Arkudas, Andreas; Horch, Raymund E.; Beier, Justus; Cai, Aijia (BMC Biotechnology, 2018)
Background: The creation of functional skeletal muscle via tissue engineering holds great promise without sacrificing healthy donor tissue. Different cell types have been investigated regarding their myogenic differentiation potential under the influence of various media supplemented with growth factors. Yet, most cell cultures include the use of animal sera, which raises safety concerns and might lead to variances in results. Electrospun nanoscaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability. We therefore aimed to develop a serum-free myogenic differentiation medium for the co-culture of primary myoblasts (Mb) and mesenchymal stromal cells derived from the bone marrow (BMSC) and adipose tissue (ADSC) on electrospun poly-ε-caprolacton (PCL)-collagen I-nanofibers. Results: Rat Mb were co-cultured with rat BMSC (BMSC/Mb) or ADSC (ADSC/Mb) two-dimensionally (2D) as monolayers or three-dimensionally (3D) on aligned PCL-collagen I-nanofibers. Differentiation media contained either AIM V, AIM V and Ultroser® G, DMEM/Ham’s F12 and Ultroser® G, or donor horse serum (DHS) as a conventional differentiation medium. In 2D co-culture groups, highest upregulation of myogenic markers could be induced by serum-free medium containing DMEM/Ham’s F12 and Ultroser® G (group 3) after 7 days. Alpha actinin skeletal muscle 2 (ACTN2) was upregulated 3.3-fold for ADSC/Mb and 1.7-fold for BMSC/Mb after myogenic induction by group 3 serum-free medium when compared to stimulation with DHS. Myogenin (MYOG) was upregulated 5.2-fold in ADSC/ Mb and 2.1-fold in BMSC/Mb. On PCL-collagen I-nanoscaffolds, ADSC showed a higher cell viability compared to BMSC in co-culture with Mb. Myosin heavy chain 2, ACTN2, and MYOG as late myogenic markers, showed higher gene expression after long term stimulation with DHS compared to serum-free stimulation, especially in BMSC/Mb cocultures. Immunocytochemical staining with myosin heavy chain verified the presence of a contractile apparatus under both serum free and standard differentiation conditions. Conclusions: In this study, we were able to myogenically differentiate mesenchymal stromal cells with myoblasts on PCL-collagen I-nanoscaffolds in a serum-free medium. Our results show that this setting can be used for skeletal muscle tissue engineering, applicable to future clinical applications since no xenogenous substances were used. <br
Keywords: Myogenic differentiation; Nanoscaffolds; Electrospun PCL-collagen I-nanofibers; Mesenchymal stromal cells; ADSC; BMSC; Myoblasts; Serum-free media

Operating on the Edge? Body Contouring Procedures in Patients with Body Mass Index Greater 35 - Hauck, Theresa; Schmitz, Marweh; Horch, Raymund E.; Arkudas, Andreas; Boos, Anja; Ludolph, Ingo; Cai, Aijia (Obesity Surgery, 2019)
Background Body contouring surgery after massive weight loss was shown to ameliorate the patient's quality of life and to enhance physical and psychological well-being. However, numerous patients are still obese when presenting for body contouring surgery, not able to lose additional weight for various reasons. Data regarding general feasibility, outcome, and postoperative complications in obese patients is rare. The aim of this study was to investigate the outcome in body contouring procedures in obese patients.
CRIS-Team WoS Importer:2019-05-24

Personalized medicine for reconstruction of critical-size bone defects – a translational approach with customizable vascularized bone tissue - Kengelbach-Weigand, Annika; Thielen, Carolina; Bäuerle, Tobias; Götzl, Rebekka; Gerber, Thomas; Körner, Carolin; Beier, Justus; Horch, Raymund E.; Boos, Anja (npj Regenerative Medicine, 2021)
Tissue engineering principles allow the generation of functional tissues for biomedical applications. Reconstruction of large-scale bone defects with tissue-engineered bone has still not entered the clinical routine. In the present study, a bone substitute in combination with mesenchymal stem cells (MSC) and endothelial progenitor cells (EPC) with or without growth factors BMP-2 and VEGF-A was prevascularized by an arteriovenous (AV) loop and transplanted into a critical-size tibia defect in the sheep model. With 3D imaging and immunohistochemistry, we could show that this approach is a feasible and simple alternative to the current clinical therapeutic option. This study serves as proof of concept for using large-scale transplantable, vascularized, and customizable bone, generated in a living organism for the reconstruction of load-bearing bone defects, individually tailored to the patient’s needs. With this approach in personalized medicine for the reconstruction of critical-size bone defects, regeneration of parts of the human body will become possible in the near future.
CRIS-Team Scopus Importer:2021-08-27

PHDs inhibitor DMOG promotes the vascularization process in the AV loop by HIF-1a up-regulation and the preliminary discussion on its kinetics in rat - Yuan, Quan; Bleiziffer, Oliver; Boos, Anja; Sun, Jiaming; Brandl, Anna; Beier, Justus; Arkudas, Andreas; Schmitz, Marweh; Kneser, Ulrich; Horch, Raymund E. (BMC Biotechnology, 2014)
The Arterovenous Loop (AV Loop) model is a vascularization model in tissue engineering research, which is capable of generating a three dimensional in vivo unit with cells as well as the supporting vessels within an isolation chmaber. In our previous studies the AV loop in the isolation chamber was discovered to undergo hypoxia, characterized by Hypoxia Inducible Factor (HIF) up-regulation. The vascularization followed the increase of HIF-? temporally, while it was spatially positively correlated with the HIF-? level, as well. This study aims to prove that HIF-1a up-regulation is the stimulus for vascularization in the AV loop model.The AV loop model in rats was created by interposing a femoral vein graft into the distal ends of the contralateral femoral artery and vein, and the loop was embeded in fibrin matrix and fixed in isolation chamber. PHD (prolyl hydroxylases) inhibitor DMOG (Dimethyloxallyl Glycine) was applied systemically in the rats in 40 mg/KG at day 0 and day 3 (DMOG-1), or in 15 mg/KG at day 8, day10 and day12 (DMOG-2). Two weeks later the specimens were explanted and underwent morphological and molecular evaluations.Compared to the control group, in the DMOG-2 group the HIF-1? positive rate was siginicantly raised as shown in immunohistochemistry staining, accompanied with a smaller cross section area and greater vessel density, and a HIF-1? accumulation in the kidney. The mRNA of HIF-1? and its angiogenic target gene all increased in different extends. Ki67 IHC demostrate more positive cells. There were no significant change in the DMOG-1 group.By applying DMOG systemically, HIF-1? was up-regulated at the protein level and at the mRNA level, acompanied with angiogenic target gene up-regulateion, and the vascularization was promoted correspondingly. DMOG given at lower dosage constantly after one week tends to have better effect than the group given at larger dosage in the early stage in this model, and promotes cell proliferation, as evidenced by Ki67 IHC. Thus, this study proves that HIF-1a up-regulation is the stimulus for vascularization in the AV loop model and that the process of the vessel outgrowth can be controlled in the AV Loop model utilizing this mechanism.
EVALuna2:15608

Plasticity of patient-matched normal mammary epithelial cells is dependent on autologous adipose-derived stem cells - Kengelbach-Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Schmid, Rafael; Marques, Jasmin Monteiro; Beier, Justus; Beckmann, Matthias; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Scientific Reports, 2019)
Due to the increasing clinical application of adipose-derived stem cells (ADSC), e.g. lipotransfer for breast reconstruction, this study aimed to gain novel insights regarding ADSC influence on breast tissue remodeling and determine patient-dependent factors affecting lipotransfer as well as begin to address its oncological risks. The ADSC secretome was analyzed from five normal breast reduction patients and contained elevated levels of growth factors, cytokines and proteins mediating invasion. ADSC/ADSC secretomes were tested for their influence on the function of primary mammary epithelial cells, and tumor epithelial cells using cell culture assays. ADSC/ADSC secretomes significantly stimulated proliferation, transmigration and 3D-invasion of primary normal and tumor epithelial cells. IL-6 significantly induced an EMT and invasion. The ADSC secretome significantly upregulated normal epithelial cell gene expression including MMPs and ECM receptors. Our study supports that ADSC and its secretome promote favorable conditions for normal breast tissue remodeling by changing the microenvironment. and may also be important regarding residual breast cancer cells following surgery.
CRIS-Team Scopus Importer:2019-08-06

Plastisch-chirurgische Rekonstruktionsverfahren des Ulcus Cruris - Boos, Anja; Hillenbrand, M.; Beier, Justus; Arkudas, Andreas; Meyer, Alexander; Lang, Werner; Horch, Raymund E. (Internistische Praxis, 2020)
The treatment of leg ulcers requires a comprehensive assessment of the patient and the underlying pathogenesis and is subject of multimodal concepts. After unsuccessful conservative treatments, the surgical wound debridement is the treatment of choice. This is complemented by local vacuum therapy or in case of chronic infected wounds by applying an instillation therapy. After adequate wound conditioning and need for plastic surgical reconstruction, minimally invasive procedures such as skin transplantation in superficial defects, up to microsurgical tissue transplantation in severe losses of substance are available. If a perfusion disorder of the affected limb is presented, a revascularisation by bypasses or AV-loops is required. With new methods in wound healing, the success rate and therefore also the quality of life of patients with chronic wounds may be improved.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Av-loop; Bypass; Free flap; Leg ulcers; Surgical therapy

Proangiogenic effects of tumor cells on endothelial progenitor cells vary with tumor type in an in vitro and in vivo rat model. - An, Ran; Schmid, Rafael; Klausing, Anne; Robering, Jan Willem; Weber, Manuel; Bäuerle, Tobias; Detsch, Rainer; Boccaccini, Aldo R.; Horch, Raymund E.; Boos, Anja; Weigand, Annika (The FASEB Journal, 2018)
Endothelial progenitor cells (EPCs) contribute to neovascularization in tumors. However, the relationship of EPCs and tumor-induced angiogenesis still remains to be clarified. The present study aimed at investigating the influence of 4 different tumor types on angiogenic properties of EPCs in an in vitro and in vivo rat model. It could be demonstrated that in vitro proliferation, migration, and angiogenic abilities and genetic modifications of EPCs are controlled in a tumor-type-dependent manner. The proangiogenic effect of mammary carcinoma, osteosarcoma, and rhabdomyosarcoma cells was more pronounced compared to colon carcinoma cells. Coinjection of encapsulated tumor cells, especially mammary carcinoma cells, and EPCs in a rat model confirmed a contributing effect of EPCs in tumor vascularization. Cytokines secreted by tumors such as monocyte chemoattractant protein 1, macrophage inflammatory protein 2, and TNF-related apoptosis-inducing ligand play a pivotal role in the tumor cell-EPC interaction, leading to enhanced migration and angiogenesis. With the present study, we were able to decipher possible underlying mechanisms by which EPCs are stimulated by tumor cells and contribute to tumor vascularization. The present study will contribute to a better understanding of tumor-induced vascularization, thus facilitating the development of therapeutic strategies targeting tumor-EPC interactions.-An, R., Schmid, R., Klausing, A., Robering, J. W., Weber, M., Bäuerle, T., Detsch, R., Boccaccini, A. R., Horch, R. E., Boos, A. M., Weigand, A. Proangiogenic effects of tumor cells on endothelial progenitor cells vary with tumor type in an in vitro and in vivo rat model.

Reconstruction of composite defects of the scalp and neurocranium-a treatment algorithm from local flaps to combined AV loop free flap reconstruction - Steiner, Dominik; Horch, Raymund E.; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Arkudas, Andreas; Schmitz, Marweh; Ludolph, Ingo; Beier, Justus; Boos, Anja (World Journal of Surgical Oncology, 2018)
BACKGROUND: Reconstruction of cranial composite defects, including all layers of the scalp and the neurocranium, poses an interdisciplinary challenge. Especially after multiple previous operations and/or radiation therapy, sufficient reconstruction is often only possible using microsurgical free flap transplantation. The aim of this study was to analyze the therapy of interdisciplinary cases with composite defects including the scalp and neurocranium. METHODS: From 2009 to 2017, 23 patients with 18 free flaps and 10 pedicled/local flaps were analyzed. First choices for free flaps were muscle flaps followed by fasciocutaneous flaps. RESULTS: Except for four patients, a stable coverage could be reached in the first operation. Three of these patients received a local scalp rotation flap in the first operation and needed an additional free flap because the local flap was no longer sufficient for coverage after wound healing deficiency or tumor relapse. The superficial temporal artery or external carotid artery served as recipient vessels. In special cases, venous grafts or an arteriovenous loop (AV loop) were used as extensions for the recipient vessels. CONCLUSIONS: In summary, an interdisciplinary approach with radical debridement of infected or necrotic tissue and the reconstruction of the dura mater are essential to reach a stable, long-lasting reconstructive result. Based on our experience, free flaps seem to be the first choice for patients after multiple previous operations and/or radiation therapy.
EVALuna2:211467

Retrospective cohort study of combined approach for trunk reconstruction using arteriovenous loops and free flaps - Arkudas, Andreas; Horch, Raymund E.; Regus, Susanne; Meyer, Alexander; Lang, Werner; Schmitz, Marweh; Boos, Anja; Ludolph, Ingo; Beier, Justus (Journal of Plastic Reconstructive and Aesthetic Surgery, 2017)
Defect reconstruction of the trunk can be performed using microsurgical free flap transplantation. In cases of missing or inappropriate recipient vessels, microsurgical defect reconstruction of the trunk can be achieved by combining free flaps with arteriovenous loops. Here we present our 5-year experience of trunk reconstruction using AV loops and free flaps in a retrospective evaluation. We analyzed 32 cases of trunk reconstruction using a combined approach of free flap transplantation and arteriovenous loops between 2011 and 2016 regarding postoperative complications and perioperative course. Twenty-one patients suffered from sternal defects, 4 from presacral defects, 3 patients presented with lateral chest wall defects, 2 patients suffered from lumbosacral defects, 1 patient had a gluteal defect and 1 patient a defect at the clavicle. In all cases, free flap transplantation and arteriovenous loop creation were performed in a two-stage procedure. There were 8 thromboses of the arteriovenous loops with 4 flap failures. Only 1 flap loss was located in the sternal region, whereas one presacral flap and both lumbosacral flaps were lost. Reconstruction of large soft tissue defects of the trunk by a combined approach with an arteriovenous loop creation and consecutive free flap transplantation represents a reliable procedure in ventral and posterior cranial localization, whereas in the caudal posterior region, AV loop thrombosis can occur. Therefore, to minimize flap loss, a two-stage procedure should be performed.
EVALuna2:15321

Scalp reconstruction: A 10-year retrospective study - Steiner, Dominik; Hubertus, A.; Arkudas, Andreas; Taeger, Christian; Ludolph, I.; Boos, Anja; Schmitz, Marweh; Horch, Raymund E.; Beier, Justus (Journal of Cranio-Maxillofacial Surgery, 2017)
Scalp reconstruction is a challenging task for the reconstructive surgeon. In consideration of the anatomical and cosmetic characteristics, the defect depth and size, an armamentarium of reconstructive procedures ranging from skin grafts over local flaps to free tissue transfer has been described. In this 10-year retrospective study, 85 operative procedures for scalp reconstruction were performed at our department. The underlying entity, defect size/depth, reconstructive procedure, complications, and mean hospital stay were analyzed. In most cases, scalp reconstruction was necessary after oncologic resection (67%) or radiation therapy (16%). A total of 85 operative procedures were performed for scalp reconstruction including local flaps (n = 50), free tissue transfer (n = 18), and skin grafts (n = 17). Regarding the complication rate, we could detect an overall major complication rate of 16.5% with one free flap loss. Briefly, local flaps are an adequate and safe procedure for limited scalp defects. In the case of extensive scalp defects affecting the calvarium, prior multiple surgical interventions and/or radiation, we prefer free tissue transfer.
EVALuna2:32851

Selective isolation and characterization of primary cells from normal breast and tumors reveal plasticity of adipose derived stem cells - Weigand, Annika; Boos, Anja; Tasbihi, Kereshmeh; Beier, Justus; Dalton, Paul D.; Schrauder, Michael; Horch, Raymund E.; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Breast Cancer Research, 2016)
There is a need to establish more cell lines from breast tumors in contrast to immortalized cell lines from metastatic effusions in order to represent the primary tumor and not principally metastatic biology of breast cancer. This investigation describes the simultaneous isolation, characterization, growth and function of primary mammary epithelial cells (MEC), mesenchymal cells (MES) and adipose derived stem cells (ADSC) from four normal breasts, one inflammatory and one triple-negative ductal breast tumors.A total of 17 cell lines were established and gene expression was analyzed for MEC and MES (n = 42) and ADSC (n = 48) and MUC1, pan-KRT, CD90 and GATA-3 by immunofluorescence. DNA fingerprinting to track cell line identity was performed between original primary tissues and isolates. Functional studies included ADSC differentiation, tumor MES and MEC invasion co-cultured with ADSC-conditioned media (CM) and MES adhesion and growth on 3D-printed scaffolds.Comparative analysis showed higher gene expression of EPCAM, CD49f, CDH1 and KRTs for normal MEC lines; MES lines e.g. Vimentin, CD10, ACTA2 and MMP9; and ADSC lines e.g. CD105, CD90, CDH2 and CDH11. Compared to the mean of all four normal breast cell lines, both breast tumor cell lines demonstrated significantly lower ADSC marker gene expression, but higher expression of mesenchymal and invasion gene markers like SNAI1 and MMP2. When compared with four normal ADSC differentiated lineages, both tumor ADSC showed impaired osteogenic and chondrogenic but enhanced adipogenic differentiation and endothelial-like structures, possibly due to high PDGFRB and CD34. Addressing a functional role for overproduction of adipocytes, we initiated 3D-invasion studies including different cell types from the same patient. CM from ADSC differentiating into adipocytes induced tumor MEC 3D-invasion via EMT and amoeboid phenotypes. Normal MES breast cells adhered and proliferated on 3D-printed scaffolds containing 20 fibers, but not on 2.5D-printed scaffolds with single fiber layers, important for tissue engineering.Expression analyses confirmed successful simultaneous cell isolations of three different phenotypes from normal and tumor primary breast tissues. Our cell culture studies support that breast-tumor environment differentially regulates tumor ADSC plasticity as well as cell invasion and demonstrates applications for regenerative medicine.
EVALuna2:15613

Specific features of ex-obese patients significantly influence the functional cell properties of adipose-derived stromal cells - Schmitz, Deborah; Robering, Jan Willem; Weisbach, Volker Günter; Arkudas, Andreas; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja; Kengelbach-Weigand, Annika (Journal of Cellular and Molecular Medicine, 2022)
Adipose-derived stromal cells (ADSC) are increasingly used in clinical applications due to their regenerative capabilities. However, ADSC therapies show variable results. This study analysed the effects of specific factors of ex-obese patients on ADSC functions. ADSC were harvested from abdominal tissues (N = 20) after massive weight loss. Patients were grouped according to age, sex, current and maximum body mass index (BMI), BMI difference, weight loss method, smoking and infection at the surgical site. ADSC surface markers, viability, migration, transmigration, sprouting, differentiation potential, cytokine secretion, telomere length and mtDNA copy number were analysed. All ADSC expressed CD73, CD90, CD105, while functional properties differed significantly among patients. A high BMI difference due to massive weight loss was negatively correlated with ADSC proliferation, migration and transmigration, while age, sex or weight loss method had a smaller effect. ADSC from female and younger donors and individuals after weight loss by increase of exercise and diet change had a higher activity. Telomere length, mtDNA copy number, differentiation potential and the secretome did not correlate with patient factors or cell function. Therefore, we suggest that factors such as age, sex, increase of exercise and especially weight loss should be considered for patient selection and planning of regenerative therapies.
CRIS-Team Scopus Importer:2022-07-22
Keywords: adipose-derived stromal cells; bariatric surgery; body mass index; cell function; regenerative medicine

The Arteriovenous (AV) Loop in a Small Animal Model to Study Angiogenesis and Vascularized Tissue Engineering - Weigand, Annika; Beier, Justus; Arkudas, Andreas; Al-Abboodi, Majida; Polykandriotis, Elias; Horch, Raymund E.; Boos, Anja (Journal of Visualized Experiments, 2016)
A functional blood vessel network is a prerequisite for the survival and growth of almost all tissues and organs in the human body. Moreover, in pathological situations such as cancer, vascularization plays a leading role in disease progression. Consequently, there is a strong need for a standardized and well-characterized in vivo model in order to elucidate the mechanisms of neovascularization and develop different vascularization approaches for tissue engineering and regenerative medicine. We describe a microsurgical approach for a small animal model for induction of a vascular axis consisting of a vein and artery that are anastomosed to an arteriovenous (AV) loop. The AV loop is transferred to an enclosed implantation chamber to create an isolated microenvironment in vivo, which is connected to the living organism only by means of the vascular axis. Using 3D imaging (MRI, micro-CT) and immunohistology, the growing vasculature can be visualized over time. By implanting different cells, growth factors and matrices, their function in blood vessel network formation can be analyzed without any disturbing influences from the surroundings in a well controllable environment. In addition to angiogenesis and antiangiogenesis studies, the AV loop model is also perfectly suited for engineering vascularized tissues. After a certain prevascularization time, the generated tissues can be transplanted into the defect site and microsurgically connected to the local vessels, thereby ensuring immediate blood supply and integration of the engineered tissue. By varying the matrices, cells, growth factors and chamber architecture, it is possible to generate various tissues, which can then be tailored to the individual patient's needs.
EVALuna2:32825

The Arteriovenous Loop: Engineering of Axially Vascularized Tissue - Weigand, Annika; Horch, Raymund E.; Boos, Anja; Beier, Justus P.; Arkudas, Andreas (European Surgical Research, 2018)
BACKGROUND: Most of the current treatment options for large-scale tissue defects represent a serious burden for the patients, are often not satisfying, and can be associated with significant side effects. Although major achievements have already been made in the field of tissue engineering, the clinical translation in case of extensive tissue defects is only in its early stages. The main challenge and reason for the failure of most tissue engineering approaches is the missing vascularization within large-scale transplants. SUMMARY: The arteriovenous (AV) loop model is an in vivo tissue engineering strategy for generating axially vascularized tissues using the own body as a bioreactor. A superficial artery and vein are anastomosed to create an AV loop. This AV loop is placed into an implantation chamber for prevascularization of the chamber inside, e.g., a scaffold, cells, and growth factors. Subsequently, the generated tissue can be transplanted with its vascular axis into the defect site and anastomosed to the local vasculature. Since the blood supply of the growing tissue is based on the AV loop, it will be immediately perfused with blood in the recipient site leading to optimal healing conditions even in the case of poorly vascularized defects. Using this tissue engineering approach, a multitude of different axially vascularized tissues could be generated, such as bone, skeletal or heart muscle, or lymphatic tissues. Upscaling from the small animal AV loop model into a preclinical large animal model could pave the way for the first successful attempt in clinical application. Key Messages: The AV loop model is a powerful tool for the generation of different axially vascularized replacement tissues. Due to minimal donor site morbidity and the possibility to generate patient-specific tissues variable in type and size, this in vivo tissue engineering approach can be considered as a promising alternative therapy to current treatment options of large-scale defects.
EVALuna2:211483

The potential role of telocytes for tissue engineering and regenerative medicine - Horch, Raymund E.; Weigand, Annika; Beier, Justus; Arkudas, Andreas; Boos, Anja (Springer New York LLC, 2016)
Despite recent advances in surgery, medicine and anaesthesiology as well as the development of microsurgical tissue transplantation, wear out of body parts remains a problem, and organ shortage does not allow to allocate enough donor organs for patients with vital diseases and conditions. The idea to create spare parts or spare organs from the patients own cells by combining engineering approaches to cellular and molecular medicine forth purpose of Tissue Engineering (TE) was fascinating when popularized in the early 1990ies. However clinically success was limited, mainly because of a lack in rapid vascularization of large scale TE replacement constructs useful for clinical purposes. The idea to utilize cells and cytokines to aid the human organism in gradually restoring lost tissue functions has drawn attention to the wider field of Regenerative Medicine (RM). Stem cells and putative stem cells, such as the recently discovered and meanwhile well described interstitial Telocytes, which are comprised of extremely long and thin prolongations named telopodes, may well become active players in the regenerative process. This article highlights the principles of TE and RM and the potential role of Telocytes with regard to tissue regeneration.
CRIS-Team Scopus Importer:2025-05-07

The potential role of telocytes in Tissue Engineering and Regenerative Medicine - Boos, Anja; Weigand, Annika; Brodbeck, Rebekka; Beier, Justus; Arkudas, Andreas; Horch, Raymund E. (Seminars in Cell & Developmental Biology, 2016)
Research and ideas for potential applications in the field of Tissue Engineering (TE) and Regenerative Medicine (RM) have been constantly increasing over recent years, basically driven by the fundamental human dream of repairing and regenerating lost tissue and organ functions. The basic idea of TE is to combine cells with putative stem cell properties with extracellular matrix components, growth factors and supporting matrices to achieve independently growing tissue. As a side effect, in the past years, more insights have been gained into cell-cell interaction and how to manipulate cell behavior. However, to date the ideal cell source has still to be found. Apart from commonly known various stem cell sources, telocytes (TC) have recently attracted increasing attention because they might play a potential role for TE and RM. It becomes increasingly evident that TC provide a regenerative potential and act in cellular communication through their network-forming telopodes. While TE in vitro experiments can be the first step, the key for elucidating their regenerative role will be the investigation of the interaction of TC with the surrounding tissue. For later clinical applications further steps have to include an upscaling process of vascularization of engineered tissue. Arteriovenous loop models to vascularize such constructs provide an ideal platform for preclinical testing of future therapeutic concepts in RM. The following review article should give an overview of what is known so far about the potential role of TC in TE and RM.
EVALuna2:15617

The role of plastic reconstructive surgery in surgical therapy of soft tissue sarcomas - Götzl, Rebekka; Sterzinger, Sebastian; Arkudas, Andreas; Boos, Anja; Semrau, Sabine; Vassos, Nikolaos; Grützmann, Robert; Agaimy, Abbas; Hohenberger, Werner; Horch, Raymund E.; Beier, Justus (Cancers, 2020)
Background: Soft tissue sarcoma (STS) treatment is an interdisciplinary challenge. Along with radio(chemo)therapy, surgery plays the central role in STS treatment. Little is known about the impact of reconstructive surgery on STS, particularly whether reconstructive surgery enhances STS resection success with the usage of flaps. Here, we analyzed the 10-year experience at a university hospital’s Comprehensive Cancer Center, focusing on the role of reconstructive surgery. Methods: We performed a retrospective analysis of STS-patients over 10 years. We investigated patient demographics, diagnosis, surgical management, tissue/function reconstruction, complication rates, resection status, local recurrence and survival. Results: Analysis of 290 patients showed an association between clear surgical margin (R0) resections and higher-grade sarcoma in patients with free flaps. Major complications were lower with primary wound closure than with flaps. Comparison of reconstruction techniques showed no significant differences in complication rates. Wound healing was impaired in STS recurrence. The local recurrence risk was over two times higher with primary wound closure than with flaps. Conclusion: Defect reconstructions in STS are reliable and safe. Plastic surgeons should have a permanent place in interdisciplinary surgical STS treatment, with the full armamentarium of reconstruction methods.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Plastic surgery; Reconstruction; Reconstructive surgery; Soft tissue sarcoma; STS

Tissue Engineering of Lymphatic Vasculature in the Arteriovenous Loop Model of the Rat - Robering, Jan Willem; Al-Abboodi, Majida; Titzmann, Adriana; Horn, Inge; Beier, Justus; Horch, Raymund E.; Kengelbach-Weigand, Annika; Boos, Anja (Tissue Engineering - Part A, 2020)
Various therapeutic approaches, for example, in case of trauma or cancer require the transplantation of autologous tissue. Depending on the size and the origin of the harvested tissue, these therapies can lead to iatrogenic complications and donor-site morbidities. In future, these side effects could be avoided by transplanting artificially generated tissue consisting of different cell types and matrix components derived from the host body. Tissue that is grown in the patient could be advantageous compared with the more simply structuredin vitro-grown alternatives. To overcome the limitations of graft vascularization, the arteriovenous (AV) loop technique has been established for different tissues in the last years and was adapted for lymphatic tissue engineering in the present study. We utilized the AV loop technique to grow human lymphatic vasculaturein vivoin the Rowett nude (RNU) rat. A combination of human lymphatic endothelial cells (LECs) and bone marrow-derived mesenchymal stem cells was implanted in a fibrin matrix surrounding the AV loop. After 2 or 4 weeks of implantation, the animals were perfused and the tissue was harvested. It could be demonstrated by immunohistochemistry for human LYVE1, human CD31, and murine podoplanin that the implanted cells formed human lymphatic vasculature in the AV loop chamber. Beside development of murine podoplanin-positive vasculature in the AV loop tissue, vasculature positive for human marker proteins developed in comparable numbers. This suggests that implanted LECs are able to improve the lymphatic vascularization of the newly engineered tissue. Thus, we were able to establish anin vivotissue engineering method to generate lymphatic vascularized soft tissue. An axially vascularized transplantable lymphatic vessel network was engineered without requiring advanced cell culture equipment, rendering the lymphatic AV loop highly suitable for applied regenerative medicine. Impact statement Various surgical procedures require the transplantation of autologous harvested tissue, for example, the vascularized lymph node transfer for the treatment of lymphedema. Tissue-engineered transplants could be used instead of autologous transplants and thereby help to reduce the side effects of those therapies. However,in vitrotissue engineering of large constructs requires a lot of know-how as well as advanced cell culture equipment, which might not be accessible in every hospital.In vivotissue engineering approaches like the presented technique for the generation of transplantable networks of lymphatic vasculature could serve as an alternative forin vitrotissue engineering approaches in clinical settings.
CRIS-Team WoS Importer:2020-10-16

Tumor‑type‑dependent effects on the angiogenic abilities of endothelial cells in an in vitro rat cell model - Al-Abboodi, Majida; An, Ran; Weber, Manuel; Schmid, Rafael; Klausing, Anne; Horch, Raymund E.; Boos, Anja; Kengelbach-Weigand, Annika (Oncology Reports, 2019)
Adequate vascularization is pivotal for tumor progression and metastasis. Tumor angiogenesis is based on a sequence of interactions between the tumor and surrounding cells and the extracellular matrix. It is widely known that a tumor can influence and control its surroundings to create favorable conditions for further growth. To investigate the influence of various tumor types on endothelial cells (ECs), an in vitro rat cell model was used and rat liver EC52 cells were co-cultured with conditioned medium derived from breast cancer MCR86, osteosarcoma ROS-1, colon cancer CC531 and rhabdomyosarcoma R1H cell lines. In a distinct tumor-type-dependent manner, the EC52 cells exhibited changes in their function and gene expression. In all functional cell culture assays (proliferation, migration, transmigration, invasion and tube formation) the breast cancer cells exerted a significant effect on the angiogenic abilities of the ECs. When comparing the various tumor cell types, only the breast and colon cancer cells led to a significant stimulation of the EC migration and invasion. Proliferation, migration, invasion and tube formation were not or only hardly influenced by the osteosarcoma or rhabdomyosarcoma cells. Similarly, the breast and colon cancer cells exhibited the strongest influence on the upregulation of EC angiogenic genes, including the ones encoding vascular endothelial growth factor A, platelet and endothelial cell adhesion molecule 1, fibroblast growth factor 2, Von Willebrand factor, C-X-C motif chemokine ligand 12 and tyrosine kinase with immunoglobulin-like and EGF-like domains 1. Therefore, it is hypothesized that tumor cells enhance the angiogenic properties of ECs, including proliferation, migration, invasion and tube formation in a tumor-type-dependent manner. This is likely based on the upregulation of pro-angiogenic genes in ECs induced by varying cytokine secretion signatures of tumor cells.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Breast cancer; Colon cancer; Endothelial cells; Osteosarcoma; Pro-angiogenic factors; Rhabdomyosarcoma; Tumor microenvironment; Tumor vascularization